Pengembangan Media Pembelajaran IPA Menggunakan Media Lectora Inspire pada Materi Pokok Panca Indera Manusia Sekolah Dasar - Heru Suprihatin; Trikinasih Handayani; Ika Maryani (Teacher in Educational Research, 2022)
This research aims to find out the feasibility of Lectora Inspire (LI) media as an IPA learning medium on the subject matter of the five human senses of elementary school fourth-grade students and know the application of IPA learning media using LI media on the subject matter of the five human senses of elementary school fourth-grade students. This research is a research and development (R&D) stage, namely: potential analysis and problems, data collection, product design, design validation, design revision, design revision, product trial, product trial revision, usage trial, and usage trial revision. The subject of this study is a student of class IV of Muhammadiyah Wirobrajan Elementary School 3 Yogyakarta. Data collection techniques use expert validation sheets, teacher questionnaire sheets, and student questionnaire sheets. The data analysis used is descriptive statistics. The results showed that IPA learning media using LI media is feasible for learning. The design validation results by media, material and learning experts get an assessment with the category "Very Feasible." The results of the application of learning media in product trials and usage trials received assessments with the category "Excellent." Based on the validation results, the results of application in product trials and trials of the use of IPA learning media using LI media are very feasible to be used for IPA learning on the subject matter of the five human senses.